POETIC SYNTAX: INTERPRETATION OF EXPRESSIVE AND EXTRALINGUISTIC MEANS (Scientific journal of the Fergana State University, 2025)
The article reveals issues of poetic syntax, which is considered one of the main areas of linguapoetics, as well as the main features of expressive and extralinguistic means involved in poetic speech, which is considered the main object of study of poetic syntax. It is also emphasized that expressiveness is another issue that should be paid attention to when studying the syntactic features of poetic speech, and the problem of expressiveness has attracted the attention of linguistic researchers for many years. Another issue that needs to be addressed within the framework of poetic syntax is the issue of extralinguistic factors influencing the creation of poetic speech. In the process of creating speech, a person does not rely only on linguistic factors to express thoughts. There are also categories that have an external influence on the formation of speech, which in linguistics are called extralinguistic factors. In general, the influence of expressive and extralinguistic means in the formation of poetic speech is noticeable in the features that we touched upon above. Only if one or another type of extralinguistic means actively influences the creation of one speech, is it inactive in another speech. Expressiveness plays an important role in the manifestation of the influence function, which is considered one of the most basic functions of language. This category is expressed in poetic speech using various linguistic units and speech means. As a result of the effective use of expressiveness in poetic speech, the formation of the effect of emotional impact has been proven.